Games and Learning Alliance Second International Conference, GALA 2013, Paris, France, October 23-25, 2013, Revised Selected Papers - De Gloria, Alessandro (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
This book constitutes the refereed proceedings of the Second International Conference on Games and Learning Alliance, GALA 2013, held in Paris, France, in October 2013. The 25 revised papers presented together with 9 poster papers were carefully reviewed and selected from numerous submissions. The papers advance the state of the art in the technologies and knowledge available to support development and deployment of serious games. They are organized in 3 research tracks on design, technology and application. Also included is the outcome of a GALA workshop on a widely applied instructional design model: 4C-ID.